(untitled) (Research, Society and Development, 2020)
The objective was to evaluate the development and reproductive performance of beef cows of different body weights at calving were evaluated. Milk yield and calf production efficiency were assessed in secundiparous Braford cows classified at calving according to weight as Light (325.2±3.7 kg), Moderate (347.7±4.0 kg), and Heavy (384.2±4.1 kg). Heavy cows had higher total milk yield than Light cows, but did not differ from Moderate, reflecting in calves weighing at weaning 82.1, 76.6, and 76.9 kg, respectively. Differences on pregnancy rates for Light (90.0%, 18 pregnant cows/2 of eligible cows), Moderate (70.2%, 12 pregnant cows/5 of eligible cows), and Heavy (62.5%, 10 pregnant cows/6 of eligible cows) were not detected. Light cows were more productive and efficient when production performance was adjusted for the pregnancy rates than Moderate and Heavy cows. Production of kilograms of calves adjusted for pregnancy was 20.5, 16.2±0.5, and 14.0±0.5 kg for the Light, Moderate, and Heavy cows, respectively. Heavy and Moderate cows were less efficient as compared with the Light ones for production of calves adjusted for their calving interval. Light cows produce more kilograms of calf/cow, requiring the same amount of milk to produce one kilogram of calf. Light cows also have higher efficiency converting milk into calf weight than Moderate and Heavy cows. The productivity and efficiency of breeding herds should be evaluated by the combination of pregnancy rate and kilograms of weaned calves per cow exposed to breeding.